ANISIAN AMMONITES FROM GEBZE AREA (KOKAELI PENINSULA, TURKEY) - NERINA FANTINI SESTINI (Rivista Italiana di Paleontologia e Stratigrafia, 2020)
Aim of the present paper is the description of an Ammonite fauna collected from the Gebze area (Kokaeli Peninsula, Turkey) by late R. Assereto in 1969 and 1971. Preliminary data on these Ammonites were reported by Assereto (1972), who in 1974 proposed the Kokaeli Peninsula, near the town of Gebze, along the Istanbul-Izmid railway-line from km 49.780 to km 51.500 as type locality of the Bithynian, a new Anisian Substage.